If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2x = 24 + -4x Solving 6 + 2x = 24 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 2x + 4x = 24 + -4x + 4x Combine like terms: 2x + 4x = 6x 6 + 6x = 24 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 6x = 24 + 0 6 + 6x = 24 Add '-6' to each side of the equation. 6 + -6 + 6x = 24 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 24 + -6 6x = 24 + -6 Combine like terms: 24 + -6 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 0.20x+0.45(70)=33.5 | | 3x^2=1-4x | | -7(x-2)-20=-6 | | 410=1015 | | b/8=90 | | 16y-9(3x-2)=0 | | 2/5(2x-1)=10 | | -9(2x-4)+22x=0 | | 4+2y=120+y | | 3(2)+8/4+5 | | 2x^2+6x+5=4 | | 14-10x=-94-45x | | 14-10x=-4-45x | | H=2+9t-5t^2 | | 2x^7/2-6=0 | | 2x7/2-6=0 | | 6+0=6*R | | Y=-1.6666666667 | | 460g/11=g | | 6+P=4*5 | | 6+29=Q*7 | | 6+2=Q*2 | | 6+3=Q*3 | | -4y+4=4(2y+6) | | -18-4x=4x+11 | | -2a+22+9a=3a-7a | | 0.2x-0.5x-5=1 | | 5(x-4)-6x= | | 6+P=5*8 | | 1=0.3x-0.6x-11 | | =-2.15 | | 6+6=4*R |